Spatiotemporal variations and source analysis of VOCs in the environmental air of a typical pesticide remediation site - Li, Xuwei; Ding, Da; Xie, Wenyi; Li, Xuzhi; Wang, Mengjie; Kong, Lingya; Jiang, Dengdeng; Deng, Shaopo (Frontiers in Environmental Science, 2023)
As efforts to mitigate soil and groundwater pollution intensify nationwide, the incidence of volatile organic compound (VOC) contaminated sites has risen significantly. These sites exhibit continuous release and dispersion of VOCs during and after remediation/control processes, thereby adversely affecting the local environment and residents. This issue has emerged as a prominent concern in contemporary society. This study takes a representative pesticide-contaminated site as the research subject. The pollutant levels, composition, spatiotemporal distribution, and source characteristics of VOCs in the ambient air environment from 2016 to 2021 were investigated by statistical analysis, Geographic Information System (GIS) spatial interpolation, Positive Matrix Factorization (PMF) model, and characteristic ratio source. The results showed that the average mass concentration proportions of the five types of pollutants are: benzene, toluene, ethylbenzene, and xylenes (BTEX) (29.73%) > alkanes (26.85%) > oxygenated hydrocarbons (21.96%) > halogenated hydrocarbons (19.12%) > sulfides (2.35%). M-/p-xylenes and toluene were the main contributing pollutants of BTEX and appeared frequently in the lists of top three pollutant in the contribution rates at various sites. The average concentration range of VOCs inside (EA1~EA5) and outside the site (CK1~CK4) were 810.71~1437.24 μg/m³, and 784.47~1358.16 μg/m³, respectively. The spatial distribution and variation trend in concentrations of halogenated hydrocarbons and alkanes were similar, with both being high in the middle of the site in 2017 and high in the south in 2018, and then sharply falling to a lower level in 2019. The source analysis results showed that the main contribution sources of environmental air varied over time. There were three types of emission sources for VOCs during the monitoring periods in 2016 and 2018. The maximum contributions to total volatile organic compounds (TVOCs) in 2016 and 2018 were volatile sources of characteristic pollutants within the site (45.6%) and volatile source of fuel (70.6%), respectively. This study provides scientific evidence for the environmental management, planning, and VOCs pollution control of pesticide-contaminated sites in China.